Anisotropy and optical gain improvement in type-II In0.3Ga0.7As/GaAs0.4Sb0.6 nano-scale heterostructure under external uniaxial strain. (October 2016) - Singh, A.K.; Riyaj, Md.; Anjum, S.G.; Yadav, Nisha; Rathi, Amit; Siddiqui, M.J.; Alvi, P.A.
Abstract: Alterations in optical transitions and distortions in wave symmetry in nano-scale QW (quantum well) heterostructures are seen due to external uniaxial strain under different polarizations. This paper reports the anisotropy phenomena and optical gain improvement realized in In0.3 Ga0.7 As/GaAs0.4 Sb0.6 type-II QW-heterostructure (well width = 20 Å) under uniaxial strain in the SWIR (short wave infra red) region. The detailed study of the band structure, wave functions associated with the charge carriers in the respective bands and optical gain under electromagnetic field perturbation is reported. The 6 × 6 diagonal k → · p → Hamiltonian matrix is evaluated and Luttinger-Kohn model is used for the band structure calculation. Optical gain spectrum in the QW-heterostructure under uniaxial strain along [110] for different polarizations of light is calculated. For a charge carrier injection of 5 × 10 12 /cm 2 the optical gain is ∼1600/cm under input z-polarization, ∼14500/cm under x-polarization and ∼15700/cm under y-polarization without external uniaxial strain applied. A significant improvement in optical gain is observed under uniaxial strain along [110] direction under different input polarizations. Keeping in views its utilization in optoelectronics due its very high optical gain in near-infra-red region in x- or y-polarization mode, such structure can be considered as a novel structure. Highlights: Very high optical gain optimization in type-II InGaAs/GaAsSb nano-scale heterostructure. Observation on anisotropic optical gain under uniaxial strain [100] within TE and TM modes. Significant improvement in interband optical gain by uniaxial strain. Shifting of operating wavelength with in mid infra red wavelength range.